Estudio de factibilidad para la creación de una empresa productora y comercializadora de frutos secos en el departamento del Quindío (2013)
The feasibility project for the creation of a company which produces and markets dry fruits in the region of Quindío, outlines the lack of awareness of the benefits of these fruits, the unsatisfied demand and low national sales of the dry fruits, and the non use of climate and suitable soils offered among others like Quindío, characteristics that demonstrate the business opportunity for the creation of the company. The overall objective of the research carried out a feasibility study, the specific objectives developed marketing, technical and engineering, organizational and legal, environmental, economic and financial studies which support the research results. The pilot test that was carried out during the preliminary project allowed to guide the research towards peanuts and almonds due to the fact that these are among the best known and consumed by the population surveyed. The marketing study revealed aspects of demand, offer, price and competitiveness, The Technical Study was essential in establishing soil and climate conditions necessary for farming dry fruits, such as peanuts and almonds in the region of Quindio, being la Tebaida the municipality that meets the characteristics for peanuts and almond farming on top of that almond, requires loose and sandy soils which are not found in the Andean region. The organizational and legal study announces the minimum organic plant for proper functioning and the set up of the company as a society for simplified actions the environmental study, includes the agricultural practices which reduce the impact on the environment and the financial economic study shows the recovery of the investment and the generation of value for the investors. The studies carried out in this research support the viability of the project.